A review of specialist palliative care provision and access across London – mapping the capital. Issue 3 (4th May 2017) - Cox, Sarah; Murtagh, Fliss E. M.; Tookman, Adrian; Gage, Andrew; Sykes, Nigel; McGinn, Maureen; Kathoria, Meeta; Wilderspin, Hilary; Chart, Liz
Abstract: Palliative care provision varies by diagnosis, geography, and setting. The Minimum Data-set provides high-level data on provision, but comprehensive comparative information about specialist palliative care (SPC) provision is lacking. The London Cancer Alliance – now RM Partners' Accountable Cancer Network - palliative care group (West/South London) and PallE8 (North/East London), with Marie Curie, sought to address this gap. The aim was to provide comparative data on SPC provision across London to support commissioners and providers to assess provision, identify gaps, and reduce inequity. A data-collection template was developed through expert consensus. Demographic, diagnostic, and service data was collected, plus models of care, staffing levels, and use of clinical outcome/experience measures. Results were collated by organisation and CCG. Cleaned data was provided back to each organisation for verification before final analyses. Results: All 50 adult SPC providers in London participated, representing hospitals, hospices and community services. Patients in all 32 CCGs have access to hospice beds, with 322 beds from 15 providers (4 NHS) for a population of 9, 323, 570 (with 47, 583 deaths annually). SPC in London sees more non-cancer patients than is reported nationally; 79% of hospital advisory, 74% of community, and 88% of hospice in-patient services have higher proportions of non-cancer patients. Considerable variation in out-of-hours availability of both hospital SPC and community SPC services across London; only 9 of 30 hospital and 17 of 26 community services provide seven-day visiting. Wide variation in the models of community-based SPC; proportions of community patients attending day services vary from 1 in 4, to 1 in 17, just 13 CCGs have H@H-type provision, with few Rapid Response or Care Coordination services. Conclusions: This detailed survey demonstrates important gaps in availability and provision of SPC services. Recommendations are made for commissioners and providers to join together to address these. It also gives a comprehensive view of rapidly changing models of community-based care, to inform innovation and service development.